2022
DOI: 10.1007/s42822-022-00101-6
|View full text |Cite
|
Sign up to set email alerts
|

Actively Addressing Systemic Racism Using a Behavioral Community Approach

Abstract: Recent police brutality and related violence against Black people, coupled with the COVID-19 pandemic, has further evidenced the disproportionate impact of systemic racism in our institutions and across society. In the United States, the alarming mortality rates for Black people due to police violence and COVID-19 related deaths are clear demonstrations of inequities within a long history of disparate outcomes. In understanding systemic racism, it is essential to consider how it is embedded within society and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…It is possible that racialized respondents reported higher rates of interference from external sources, such as from workplace policy and senior management, because these sources can perpetuate racism and systemic discrimination (Walter et al 2017;Watson-Thompson et al 2022). Discriminatory policies can disadvantage racialized groups by interfering with their ability to conduct and disseminate their work, practice public commentary, impact social well-being, researcher retention, and, as suggested by the data, make them more fearful of negative career consequences due to public commentary (Miller and Garran 2007;Miriti 2020;Watson-Thompson et al 2022). This was exemplified by PARID 164: "I am a member of a cultural minority.…”
Section: Racialized Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that racialized respondents reported higher rates of interference from external sources, such as from workplace policy and senior management, because these sources can perpetuate racism and systemic discrimination (Walter et al 2017;Watson-Thompson et al 2022). Discriminatory policies can disadvantage racialized groups by interfering with their ability to conduct and disseminate their work, practice public commentary, impact social well-being, researcher retention, and, as suggested by the data, make them more fearful of negative career consequences due to public commentary (Miller and Garran 2007;Miriti 2020;Watson-Thompson et al 2022). This was exemplified by PARID 164: "I am a member of a cultural minority.…”
Section: Racialized Groupsmentioning
confidence: 99%
“…Impacts of interference on research, researchers, and the integrity of science Significant differences were observed across 11 of the 25 quantitative measures. This is a concern as interference can impact the well-being of researchers themselves, especially for marginalized researchers, many of whom are already dealing with compounding challenges in the workplace due to identity-related discrimination and stress (Baumgärtner et al 2015;Dyer et al 2019;Fine et al 2020;Cech and Waidzunas 2021;Watson-Thompson et al 2022). These impacts can have serious repercussions on researchers' mental health, job satisfaction, researcher retention, and cause moral compromise (Hall et al 2019;Miriti 2020;Driscoll et al 2021;Robertson et al 2023).…”
Section: Slgbtqi+mentioning
confidence: 99%
“…Apesar do racismo institucional estar intimamente ligado ao racismo estrutural, esses termos não devem ser utilizados como análogos. O racismo institucional é um produto do racismo estrutural, sendo, o último mais amplo, pois inclui a história, cultura, contexto socioeconômico, sistemas políticos e normas sociais que permitem a desigualdade racial (Watson-Thompson et al, 2022). As instituições são um espelho do nosso sistema político e das normas sociais, por isso, reproduzem essas práticas, o que resulta em muitos dos problemas enfrentados pelos negros na saúde, educação, economia e nos sistemas de justiça (Parks & Kirby, 2022).…”
Section: Racismo Institucionalunclassified